A Study on Science Teachers’ Perception of Newly Developed Science Workbooks and Their Effectiveness in Fostering Scientific Attitude in Learners - Seema Lenin Koshy; Shruti Tiwari (International Journal of Education Sciences, 2025)
This study examines science teachers’ perceptions of newly developed science workbooks and evaluates their effectiveness in fostering scientific attitude among learners. Using a structured opinionnaire, the research gathered comprehensive feedback from teachers across multiple grade levels regarding the clarity, relevance, and pedagogical value of the workbooks. Analysis of opinionnaire responses revealed strong teacher agreement regarding the workbook’s clarity, activity-based structure, and alignment with curriculum goals. Teachers reported noticeable improvements in students’ curiosity, observation skills, and evidence-based reasoning. Moreover, teachers noted that the workbook’s emphasis on hands-on engagement and problem-solving encouraged active participation and deeper conceptual grasp among learners. The workbooks’ structured tasks, reflective questions, and real-life applications were identified as key contributors to enhanced scientific thinking. Findings demonstrate that positive teacher perception significantly influences workbook adoption and learning outcomes, reinforcing the importance of well-designed, inquiry-centered instructional materials in promoting scientific attitude. The study confirms that well-designed, inquiry-centered workbooks can significantly promote scientific attitude and support the development of essential 21st-century skills. These results highlight the need for continued innovation in educational resource design to strengthen science pedagogy and improve learning outcomes.
Keywords: Science workbooks; national education policy; opinionnaire; overall assessment; teaching-learning process